2021
DOI: 10.1155/2021/5744656
|View full text |Cite|
|
Sign up to set email alerts
|

Data Mining-Based Stability and Prescription Analysis of Neonatal Parenteral Nutrition Solution

Abstract: In order to evaluate the stability of neonatal parenteral nutrition solution, in this paper, the prescription of neonatal parenteral nutrition solution was investigated and analyzed. The formula of neonatal parenteral nutrition solution used, particularly the one utilized in this study, is commonly used in clinical practice. All the neonatal parenteral nutrition solution required for the test was prepared on the purification workbench in a sterile environment. The time points of stability of parenteral nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%